Dietary Qiwenghuangbo powder–enriched Limosilactobacillus reuteri protects the intestinal epithelium and alleviates inflammation via a strain‐specific mechanism - Qian Xu; Lei Xue; Zhenhua Wu; Shuaishuai Kang; Jia Li; Yifan Wu; Yujun Wu; Jinbiao Zhao; Rujuan Wu; Huiyuan Lv; Junjun Wang; Dandan Han (Animal Models and Experimental Medicine)
Abstract Background Qiwenghuangbo powder (QP), composed of Astragalus, Phellodendron chinensis, and Radix pulsatilla, is a traditional Chinese herbal formula, but its effects on weaned piglets remained unclear. Methods Weaned piglets fed with 0.5 kg/t QP (QP1), 1 kg/t QP (QP2), low‐zinc oxide (ZnO; negative control), and high‐ZnO (positive control) diets in two phases, respectively, and the growth performance, intestinal morphology, cytokines, and microbial communities were profiled. The mouse models of colitis induced by Citrobacter rodentium and dextran sulfate sodium (DSS) were employed to elucidate the potential role of QP‐fed enriched key species. Results Dietary 1.0 kg/t QP alleviated diarrhea and inflammation and improved intestinal development and growth performance of weaned piglets. Moreover, this dietary intervention notably altered microbiota composition, characterized by the enrichment of Limosilactobacillus reuteri. Furthermore, out of three isolated L. reuteri, two strains could alleviate pathogen infection and intestinal inflammation, respectively. Specifically, the anti‐inflammatory effect of one strain was achieved by promoting the colonization resistance of C. rodentium as significantly reduced pathogen loads. The other strain mitigated DSS‐induced colitis by enhancing the goblet cell function and inhibiting the secretion of pro‐inflammatory cytokines, particularly interleukin‐1β (IL‐1ß) and tumor necrosis factor‐α (TNF‐α). Conclusions Dietary QP improved the growth performance and intestinal health of weaned piglets by promoting the colonization of L. reuteri. The isolated commensal L. reuteri control colitis in a strain‐specific mechanism, highlighting the potential of QP and L. reuteri in providing evidence for gut health promotion.